Prevention of Jarisch-Herxheimer reactions by treatment with antibodies against tumor necrosis factor alpha. - Fekade, D; Knox, K; Hussein, K; Melka, A; Lalloo, D; Coxon, R; Warrell, D (1996)
BACKGROUND: In patients with louse-borne relapsing fever (Borrelia recurrentis infection), antimicrobial treatment is often followed by sudden fever, rigors, and persistent hypotension (Jarisch-Herxheimer reactions) that are associated with increases in plasma concentrations of tumor necrosis factor alpha (TNF-alpha), interleukin-6, and interleukin-8. We attempted to determine whether sheep polyclonal Fab antibody fragments against TNF-alpha (anti-TNF-alpha Fab) could suppress the Jarisch-Herxheimer reaction. METHODS: We conducted a randomized, double-blind, placebo-controlled trial in 49 patients with proven louse-borne relapsing fever. Immediately before the intramuscular injection of penicillin, the patients received an intravenous infusion of either anti-TNF-alpha Fab or a control solution. RESULTS: Ten of the 20 patients given anti-TNF-alpha Fab had Jarisch-Herxheimer reactions with rigors, as compared with 26 of the 29 control patients (P = 0.006). The controls had significantly greater mean maximal increases in temperature (1.5 vs. 0.8 degrees C, P < 0.001), pulse rate (31 vs. 13 per minute, P < 0.001), and systolic blood pressure (25 vs. 15 mm Hg, P < 0.003), as well as higher mean peak plasma concentrations of interleukin-6 (50 vs. 17 micrograms per liter) and interleukin-8 (2000 vs 205 ng per liter) (P < 0.001 for both comparisons). Levels of TNF-alpha were undetectable after treatment with anti-TNF-alpha Fab. CONCLUSIONS: Pretreatment with sheep anti-TNF-alpha Fab suppresses Jarisch-Herxheimer reactions that occur after penicillin treatment for louse-borne relapsing fever, reduces the associated increases in plasma concentrations of interleukin-6 and interleukin-8, and may be useful in other forms of sepsis.